Synthesis of Some New Diaryl and Triaryl Hydrazone Derivatives as Possible Estrogen Receptor Modulators - Pandey, Jaya; Pal, Rekha; Dwivedi, Anila; Hajela, Kanchan (Arzneimittelforschung, 2002)
l,2-Bis(4-substituted phenyl)-2-methyl ethanone (2,4-dlnitrophenyl)hydrazones and 1-naphthyl-1-(4-substituted phenyl)-methanone (2,4-dinitrophenyl)hydrazones have been synthesized and evaluated for their anti-implantation, uterotrophic, antiuterotrophic, anticancer and antimicrobial activities. Diphenolic hy-drazone (compound 6) showed maximum uterotrophic inhibition of 70 %, whereas compound 20 exhibited cytotoxicity in the range of 50–70 % against MCF-7 and ZR-75-1 human malignant breast cell lines.
Keywords: Estrogen receptor modulators; Hydrazones, anticancer studies, anti-implantation studies, antimicrobial studies; synthesis, uterotrophic studies